2001
DOI: 10.1161/01.str.32.2.466
|View full text |Cite|
|
Sign up to set email alerts
|

Tolerability of the Low-Affinity, Use-Dependent NMDA Antagonist AR-R15896AR in Stroke Patients

Abstract: Background and Purpose-AR-R15896AR is a use-dependent, low-affinity blocker of the NMDA ion channel with neuroprotective effects in animal models of focal cerebral ischemia. This study aimed to establish the highest safe and tolerated loading and maintenance dosing regimen of AR-R15896AR in acute ischemic stroke patients and to determine the associated plasma concentrations of AR-R15896AR. Methods-This was a 4-part, multicenter, randomized, double-blind, placebo-controlled study in 175 patients (mean age, 69 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 32 publications
0
17
0
1
Order By: Relevance
“…3,16 N-Methyl-D-aspartate receptor antagonists also failed to fill their optimistic prognosis, as none of the treatments that showed preclinical promise are available to date. 17,18 The maintenance of brain extracellular Glu at levels below its excitotoxic threshold is performed not only by Glu transporters located on glia and neurons but also by those present on the antiluminal side of the brain capillary endothelial cells. 19,20 These transporters remove the excess extracellular brain Glu into the blood stream.…”
Section: Introductionmentioning
confidence: 99%
“…3,16 N-Methyl-D-aspartate receptor antagonists also failed to fill their optimistic prognosis, as none of the treatments that showed preclinical promise are available to date. 17,18 The maintenance of brain extracellular Glu at levels below its excitotoxic threshold is performed not only by Glu transporters located on glia and neurons but also by those present on the antiluminal side of the brain capillary endothelial cells. 19,20 These transporters remove the excess extracellular brain Glu into the blood stream.…”
Section: Introductionmentioning
confidence: 99%
“…This might raise a concern taking into account the neurotoxic properties reported from a study in stroke with another NMDA antagonist [4]. However, in an earlier study in stroke patients a lower mortality rate was observed in the AR-R15896AR group [10]. As expected the primary cause of death was the neurological damage from the initial stroke.…”
Section: Discussionmentioning
confidence: 90%
“…Ascending loading and maintenance doses were tested in 175 patients with acute ischaemic stroke [10]. A loading dose of 250 mg AR-R15896AR and maintenance doses of 120 mg tid for three days were well tolerated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mild-tomoderate hypothermia with cooling to 331C initiated within 2 h of cardiac arrest (Bernard et al, 2002) increased the likelihood of a good outcome (26-49%). The clinical development of AR-R15896AR was discontinued after phase II studies demonstrated adverse effects of dizziness, vomiting, nausea, stupor, agitation and hallucinations at plasma concentrations just after achieving the neuroprotective plasma concentrations (Lees et al, 2001;Diener et al, 2002). These adverse effects were seen with other NMDA antagonists taken through to clinical development and were a limiting factor in optimizing dosing (Muir and Lees, 1995).…”
Section: Systematically Reviewing Preclinical Data and Stair Criteriamentioning
confidence: 99%